Pengaruh Flypaper Effect pada dana alokasi umum (DAU) dan pendapatan asli daerah (PAD) terhadap Pertumbuhan Ekonomi di Kota Banda Aceh (Studi Empiris pada Pemeritah Kota Banda Aceh Tahun 2008-2014) - Mulya, Rahmatul; Bustamam, Bustamam (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this research is to examine and analyze the influence of the relationship flypaper to economic growth by the Regional Government of Banda Aceh. The research type used is a correlational study by sensus method. The results of this research shows that the (1) flypaper on PAD and flypaper on DAU simultaneously affect the economic growth in allocation to capital expenditures (2) flypaper on PAD positive effect on economic growth in allocation to capital expenditures. (3) GCG flypaper on DAU negatively affect economic growth in allocation to capital expenditures. Keyword: Flypaper effect, PAD, DAU, Capital Expenditures, Economic Growth.